Assessment of health behaviours in family nurses - Magdalena Zych; Wiesław Marian Fidecki; Mariusz Wysokiński; Dorota Kulina; Zofia Sienkiewicz; Katarzyna Zuń; Aneta Jędrzejewska; Agnieszka Kijowska (Kazimierz Wielki University, 2019)
Introduction. Health behaviours are understood as any behaviours (habits, attitudes, customs, values) that are concerned with health. Pro-health behaviours are all deliberate activities aimed at maintaining or improving health. Aim. The aim of the research was the determination of health behaviours in family nurses. Material and method. The research was performed in 152 family nurses from the Lublin and Mazovian Region by means of Health Behaviour Inventory (the HBI). The research tool comprises 24 items in four categories: proper eating habits, preventive health behaviours, health practices, positive attitude. Results. The mean value of health behaviours indicator in the group researched was 85.86 points. A total of 49.34% of nurses presented a high level of health behaviours. The group of 40.97% of family nurses were individuals who depicted a moderate level of health behaviours. Merely 9.87% of the nurses researched showed a low level of health behaviours. On the basis of the analysis of the data collected it was found that preventive health behaviours were rated the highest (3.76 points), whereas health practices were rated the lowest (3.36 points). Proper eating habits and positive attitude were determined on a very similar level. Conclusion. The family nurses researched showed moderate level of health behaviours. The best results were obtained in preventive health behaviours, whereas health practices were rated the lowest. Professional experience of the nurses affected their health behaviours in terms of preventive behaviours.